Atmospheric cold plasma frequency imparts changes on cashew apple juice composition and improves vitamin C bioaccessibility. (September 2021) - K. F. Leite, Ana; Fonteles, Thatyane V.; B.A.R. Miguel, Thaiz; Silvestre da Silva, Giselle; Sousa de Brito, Edy; Alves Filho, Elenilson G.; Fernandes, Fabiano A.N.; Rodrigues, Sueli
Graphical abstract: Highlights: Atmospheric Cold Plasma (ACP) decreased the sugar concentration. The excitation frequency affected the juice composition. ACP promoted an increase of compounds mainly in the gastric phase of digestion. ACP improved the vitamin C bioaccessibility. The in vitro digestion did not affect the phenolic bioaccessibility. Abstract: This study evaluated the atmospheric cold plasma (ACP) effect on cashew apple juice composition at different frequencies (200 and 700 Hz). The impact of this non-thermal technology on the organic juice compounds after the processing and along with the in vitro digestion carried out in a simulated digestion system at 37 °C/6 h was evaluated. The changes in the juice composition were determined by NMR spectroscopy and chemometric analyses. Vitamin C and total phenolic compounds were also quantified in processed and non-processed (control) juices and after each digestion phase. The results showed decreased glucose and fructose in samples treated by ACP and an increment in malic acid concentration for ACP700. ACP increased the amount of vitamin C in the juices and did not affect the total phenolic content. The gastric digestion highlighted the pronounced effect of plasma on the juice composition, increasing all of the components detected by NMR. Cashew apple juice processed by ACP700 presented a higher concentration of malic acid and phenylalanine. An increased bioaccessibility of vitamin C was also found for ACP700. Although ACP processing has decreased some compounds' concentration, this technology improved the bioaccessibility of vitamin C – the main bioactive compound of cashew apple juice.